Land use, environment, and development experiences from the Chittagong Hill Tracts of Bangladesh - Rasul, Golam (Dhaka : A.H. Development Pub. House ; Kolkata : Distributor in India, Paragon Enterprise, 2009)
Study focused on Chittagong Hill Tracts, Region, Bangladesh.
Includes bibliographical references (p. [213]-234) and index.
Keywords: Land tenure -- Bangladesh -- Chittagong Hill Tracts (Region); Agriculture -- Economic aspects -- Bangladesh -- Chittagong Hill Tracts (Region)